Arsenic removal from drinking water using wood charcoal - Ali, Md Hannan; Islam, Md Hamidul; Huda, Md Sanaul; Ali, Md Rostom (Fundamental and Applied Agriculture, 2018)
Arsenic contamination of drinking water is threatening the health of millions of people of Bangladesh. Lack of appropriate arsenic removal technology has complicated and inhibited the mitigation initiatives. The effectiveness of wood charcoal for removal of arsenic from tubewell water was evaluated in this study. Arsenic contaminated water sample was passed through a pitcher having a small hole at its bottom contained wood charcoal at a controlled flow rate of 30 mL min−1 with different thickness of wood charcoal (7.5, 10, 12.5, 15, 17.5, 20 and 22.5 cm) and at different flow rates (10, 30, 50, 70, 90, 110 and 130 mL min−1) with 20 cm fixed thickness of wood charcoal. Results revealed that with the increased of flow rate the removal of arsenic percentage decreased. Maximum arsenic removal efficiency (93.68%) was obtained at a flow rate of 10 mL min−1 with 20 cm of charcoal thickness. In addition, it was also observed that both flow rate and charcoal thickness are critically important in achieving higher arsenic removal efficiency. Therefore, water flow rate of 50 mL min−1 with charcoal thickness of 15 cm could be used to remove arsenic from contaminated tube well water (arsenic concentration after filtration was 30 μg L−1 which is below the allowable arsenic concentration standard i.e. 50 μg L−1).